Engineered organoids for biomedical applications - Roberto de Barros, Natan; Wang, Canran; Maity, Surjendu; Peirsman, Arne; Nasiri, Rohollah; Herland, Anna; Ermis, Menekse; Kawakita, Satoru; Gregatti Carvalho, Bruna; Hosseinzadeh Kouchehbaghi, Negar; Donizetti Herculano, Rondinelli [UNESP]; Tirpáková, Zuzana; et al. (Elsevier, 2023)
As miniaturized and simplified stem cell-derived 3D organ-like structures, organoids are rapidly emerging as powerful tools for biomedical applications. With their potential for personalized therapeutic interventions and high-throughput drug screening, organoids have gained significant attention recently. In this review, we discuss the latest developments in engineering organoids and using materials engineering, biochemical modifications, and advanced manufacturing technologies to improve organoid culture and replicate vital anatomical structures and functions of human tissues. We then explore the diverse biomedical applications of organoids, including drug development and disease modeling, and highlight the tools and analytical techniques used to investigate organoids and their microenvironments. We also examine the latest clinical trials and patents related to organoids that show promise for future clinical translation. Finally, we discuss the challenges and future perspectives of using organoids to advance biomedical research and potentially transform personalized medicine.
Keywords: Disease modeling; Organoids; Regenerative medicine; Spheroids; Stem cell; Therapies